Efek samping pada rongga mulut akibat terapi siklosporin Side effect in oral cavity due to cyclosporine therapy - Rifi Aranti; Yulianti Kemal (DiscoverSys Inc., 2013)
Cyclosporine is an immunosuppressant drug that suppresses effectively the immune response, and main drug used toprevent rejection in organ transplantation. Negative impact in the oral cavity of cyclosporine therapy is characterizedby the occurrence of gingival enlargement in 8-70% of cases, which occurred in the first 3-6 months of use, as well asthe loss of alveolar bone. The effect of the drug on gingival enlargement is a serious problem in patients receivingcyclosporine therapy. Pathogenesis of gingival enlargement on cyclosporine therapy is not known at all, but theinfluence of fibroblast proliferation and extracellular matrix were estimated reduction capabilities play a role in thisaspect. Dental plaque does not have a significant relationship to the occurrence of gingival enlargement oncyclosporine therapy, but support the occurrence of chronic inflammation that contributes to gingival enlargement.Adequate oral hygiene with initial periodontal treatment can reduce inflammation and gingival enlargement due tocyclosporine therapy. Patients who will undergo organ transplantation, previously had to undergo dental and oralhealth care comprehensively.